Indikasi Moral Hazard dan Strategi Mitigasi Risiko dalam Pembiayaan Mudharabah pada Perbankan Syariah di Indonesia - Rahardiansyah, Risal Fadhil; Purnamaputra, Muhammad Zulkarnaen; Dhea, Putri Ayu; Wilujeng, Putri Sasya (Al-Muhasib: Journal of Islamic Accounting and Finance, 2022)
Mudharabah financing contract is one of the main products of sharia banking. As a contract that relies on cooperation, it is required in this contract to include the agreement and the necessary conditions between the fund owner and the fund manager at the beginning of the agreement. This study aims to explore and reveal the existence of Moral Hazard in Mudharabah financing in Indonesia’s Islamic Banking as well as the risk mitigation strategies that can be carried out. The systematic literature review (SLR) method is used in this study with the aim of collecting records on the occurrence of Moral Hazard that has occurred in Islamic Banking in Indonesia. The data is presented in a qualitative descriptive manner with the object of research being several Islamic banks in Indonesia. Based on the research that has been done, there are internal and external factors that can cause moral hazard. One of the risk mitigation strategies that can be carried out is the Early Warning System Before Transaction, which is to tighten the feasibility analysis of potential customers with on site monitoring..   Keywords: Moral Hazard; Risk Mitigation; Mudharabah; Sharia Bank